Analysis of the Choice of Transportation Modes from Lhokseumawe City to Medan City Using the Analytical Hierarchy Process Method - Afdal, Muhammad; Ridwan, Teuku Muhammad; Malasyi, Syibral; Savira Ersa, Nanda; Burhanuddin, Burhanuddin; Fadhliani, Fadhliani; Chandra, Yovi (International Journal of Engineering, Science and Information Technology, 2025)
Inter-provincial movement activities from Lhokseumawe to Medan are busy travel routes because land routes connect many cities. Minibusses and buses serve transportation needs across these cities. Travelers choose minibusses because of their convenience, fast travel time, and comfort. The bus mode also offers smooth and comfortable travel, making it a popular choice among travelers on the Lhokseumawe to Medan route. This research aims to determine the characteristics and percentage of transportation mode choices by travelers. The approach used is the analytical hierarchy process method. The results of the analysis showed that the percentage of travelers interested in choosing a particular mode resulted in 42% of passengers choosing the Hiace Minibus, 24% selecting the Sempati Star Bus, 20% choosing the Putra Pelangi Bus, and 14% selecting the Kurnia Bus. The criteria that influence the choice of transportation mode are convenience with a percentage of 22%, time with a percentage of 19%, comfort with a percentage of 16%, cost with a percentage of 15%, headway and safety with a percentage of 14%.